2012
DOI: 10.1116/1.4737155
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of vertical Si nanowire p-n diodes fabricated by metal-assisted etching and AAO templates

Abstract: Articles you may be interested inInfluence of catalytic gold and silver metal nanoparticles on structural, optical, and vibrational properties of silicon nanowires synthesized by metal-assisted chemical etching Fabrication of vertically aligned Si nanowires on Si (100) substrates utilizing metal-assisted etching J. Vac. Sci. Technol. A 28, 735 (2010); 10.1116/1.3336572Integrated silicon nanowire diodes and the effects of gold doping from the growth catalyst Vertical Si nanowire p-n diodes were fabricated utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…For a more detailed discussion about the possible mechanism for MACE, see the article by Geyer et al [ 46 ] Typically, the process results in the formation of silicon nanopillars with diameters from <10 nm up to a few hundred nanometers, and with heights depending on the etching time, ranging from a few micrometers up to 20 µm. [ 2,[47][48][49] Peng et al investigated the etching direction of both gold and silver particles, and concluded that this direction is highly uniform, does not depend on the dopant type and level of the substrate, and preferentially occurs along the (100) orientation of crystalline silicon ( Figure 6 ). [ 50 ] Instead of electroless deposition of metal particles, it is also possible to deposit a thin metal fi lm, which is patterned or annealed to create nanoparticles.…”
Section: Reviewmentioning
confidence: 99%
“…For a more detailed discussion about the possible mechanism for MACE, see the article by Geyer et al [ 46 ] Typically, the process results in the formation of silicon nanopillars with diameters from <10 nm up to a few hundred nanometers, and with heights depending on the etching time, ranging from a few micrometers up to 20 µm. [ 2,[47][48][49] Peng et al investigated the etching direction of both gold and silver particles, and concluded that this direction is highly uniform, does not depend on the dopant type and level of the substrate, and preferentially occurs along the (100) orientation of crystalline silicon ( Figure 6 ). [ 50 ] Instead of electroless deposition of metal particles, it is also possible to deposit a thin metal fi lm, which is patterned or annealed to create nanoparticles.…”
Section: Reviewmentioning
confidence: 99%
“…[10][11][12][13][14] Among these materials, anodic aluminum oxide (AAO) template has great advantages due to the low cost and easy process. [10][11][12] Especially, AAO templates provide good opportunities to fabricate high-density arrays of sizecontrolled nanodots on a Si substrate by depositing the materials on a through-hole membrane. 10 In this study, we fabricated Cr nanodot Schottky diodes by depositing Cr through AAO templates.…”
Section: Introductionmentioning
confidence: 99%
“…For a more detailed discussion about the possible mechanism for MACE, see the article by Geyer et al [46] Typically, the process results in the formation of silicon nanopillars with diameters from <10 nm up to a few hundred nm, and with heights depending on the etching time, ranging from a few µm up to 20 µm. [2,[47][48][49] Peng et al investigated the etching direction of both gold and silver particles, and concluded that this direction is highly uniform, does not depend on the dopant type and level of the substrate, and preferentially occurs along the (100) orientation of crystalline silicon (Figure 2.6). [50] Instead of electroless deposition of metal particles, it is also possible to deposit a thin metal film, which is patterned or annealed to create…”
Section: Wet Etchingmentioning
confidence: 99%